IMPLEMENTASI MATERI MAHÂRAH AL-KALÂM DALAM TRANSFORMASI KURIKULUM BAHASA ARAB PERSPEKTIF ACTFL PADA PONDOK PESANTREN SALAF - Husna, Muhammad Ahsanul; Inayah, Inayah; Mubarak, Faisal; Taufiqurrahman, Taufiqurrahman; Qomariyah, Lailatul (Arabi : Journal of Arabic Studies, 2022)
Most Arabic language studying at Salaf Islamic Boarding Schools leads to maharah al-qira'ah wa al-istima'. One of the salaf Islamic boarding schools, namely Raudlatul Ulum Guyangan Pati, Central Java, Indonesia, began the formulation of curriculum transformation by achieving the goals of speaking skills (maharah al-kalam). This study aimed to analyze the implementation of maharah al-kalam material of the ACTFL Perspective Arabic language curriculum at the Raudlatul Ulum Islamic Boarding School. The method uses a qualitative explanatory case study approach. The implementation of maharah al-kalam material follows four curriculum management stages: planning, organization, performance, and evaluation. The results show (1) planning: preparation of muhādaṡah materials 2JP, debates, and speeches based on: (a) vision and mission, (b) goals of maharah al-kalam, (c) developing students' talents; (2) organization: material using al-'Arabiyyah Bayna Yadaik; (3) performance: learning process uses direct, audiolingual, mixed methods supporting bī'ah, native speakers, laboratories, kitab turats; (4) evaluation using imtihān and munaqasyah.